Perbandingan Pengaturan Tindak Pidana Korupsi dalam Pembaharuan KUHP Nasional - Meidiantama, Refi; Charinda, Donna Exsanti (Kajian Ilmiah Hukum dan Kenegaraan, 2024)
Purpose: This study analyzes updates and comparative changes in the regulation of corruption crimes, focusing on the transition from the Corruption Eradication Law to the New Criminal Code. Methodology: A normative juridical approach is employed, utilizing both primary and secondary sources. Primary data is obtained through interviews with key informants, while secondary data is drawn from literature, including books, academic studies, and journal publications. Results: The findings reveal significant changes in the regulation of criminal sanctions related to corruption, particularly in terms of imprisonment and financial penalties. These shifts are evident in the transition from the previous Corruption Law to the updated provisions under the New Criminal Code, specifically Articles 603 and 604. Notably, certain provisions show a reduction in the minimum terms of imprisonment and fine amounts. Conclusion: While some sanctions—such as maximum prison terms for bribery and fines for gratification—have increased, the overall trend in the New Criminal Code is toward more lenient penalties compared to the earlier legal framework. Limitations: This study is limited to a legal comparison between the Corruption Eradication Law and the provisions of the New Criminal Code. Contribution: The study contributes to legal scholarship by offering a comparative analysis of recent developments in corruption-related criminal law, supporting improved understanding and enforcement of anti-corruption regulations.